2020
DOI: 10.3390/cancers12030632
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Integration Analysis Revealed Presence of Novel Prognostic miRNA Targets and Important Cancer Driver Genes in Triple-Negative Breast Cancers

Abstract: Background: miRNAs (microRNAs) play a key role in triple-negative breast cancer (TNBC) progression, and its heterogeneity at the expression, pathological and clinical levels. Stratification of breast cancer subtypes on the basis of genomics and transcriptomics profiling, along with the known biomarkers’ receptor status, has revealed the existence of subgroups known to have diverse clinical outcomes. Recently, several studies have analysed expression profiles of matched mRNA and miRNA to investigate the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Moreover, NAT1 was positively correlated with ER and PR expression, negatively correlated with BC tumor grade and size, and associated with longer survival in BC patients treated with tamoxifen and in patients with lymph node metastasis [237]. Interestingly, integrated analysis indicated that miR-1290 was downregulated in TNBC; however, its expression was correlated with poor prognosis, which suggests the high variability of miRNA expression within this subtype [238]. The above conclusion was supported by a significant inverse correlation of miR-1290 with FOXA1, one of the highly upregulated genes in the analyzed TNBC group.…”
Section: Female Cancers 731 Breast Cancermentioning
confidence: 99%
“…Moreover, NAT1 was positively correlated with ER and PR expression, negatively correlated with BC tumor grade and size, and associated with longer survival in BC patients treated with tamoxifen and in patients with lymph node metastasis [237]. Interestingly, integrated analysis indicated that miR-1290 was downregulated in TNBC; however, its expression was correlated with poor prognosis, which suggests the high variability of miRNA expression within this subtype [238]. The above conclusion was supported by a significant inverse correlation of miR-1290 with FOXA1, one of the highly upregulated genes in the analyzed TNBC group.…”
Section: Female Cancers 731 Breast Cancermentioning
confidence: 99%
“…For instance, an 8-miRNAs signature (miR-139-5p, miR-10b-5p, miR-486-5p, miR-455-3p, miR-107, miR-146b-5p, miR-324-5p and miR-20a-5p) supported an accurate predictive model of relapse in TNBC patients highly correlated with prognosis (AUC of 0.80), independently validated twice (AUCs of 0.89 and 0.90) ( 32 ). In study of Zaka et al ( 33 ), Cox analysis was employed to identify 25 miRNAs associated with prognosis with both risky and protective outcomes. Some miRNAs were associated with OS (hsa-miR-342-3p, hsa-miR-195, hsa-miR-155, and hsa-miR-497) and others with distant metastases-free survival (hsa-miR-29c, hsa-miR-342-3p, hsa-let-7c, hsa-let-7b, and hsa-miR-497).…”
Section: Contextualizationmentioning
confidence: 99%
“…The omics-driven and network-based approaches, composed of biological and computational processes, can lead to the more precise discovery of potential novel biomarkers due to corroborative evidence integrated with interacting molecular entities and incorporating measurements of molecule expression and biological function ( 18 21 ). The miRNA targeting topology networks are frequently used to extract key miRNAs from noisy backgrounds for further translational studies ( 22 , 23 ). In contrast to this approach, Chen et al ( 24 ) increased our understanding of miRNA biology by developing a single-line regulatory miRNA vulnerability network and identifying the corresponding biomarkers.…”
Section: Introductionmentioning
confidence: 99%